Contextualizing educational innovation: Task-based language teaching and post-soviet schools in Ukraine - Bogachenko, Tetiana (Curtin University, 2016)
This qualitative study explores foreign language teaching in post-Soviet schools in Ukraine to provide insights into whether and how task-based approach (TBLT) can be contextualized to become an appropriate innovation in this setting. Based on policies, practices, and teacher perceptions, a description of the local FLT context was provided and the potential benefits and challenges of TBLT in this particular setting were identified. These have implications for the local pedagogy, innovation management, and TBLT implementation.